A study of a group intervention for postnatal depression at a community health care centre - Krauss, Rosa (Department of Social Development, 2014)
Untreated postnatal depression may have serious and long-lasting consequences for mother and infant. These range from feelings of inadequacy and worthlessness in the mother to social, emotional, cognitive and behavioural disturbances in her child. Postnatal depression is also associated with maternal and infant death. In South Africa, postnatal depression is not screened for as a matter of routine and many women go undiagnosed and untreated. The research was conducted at a community health centre using a mixed methodology of quantitative and qualitative techniques. A sample of six women with postnatal depression participated in a group intervention programme for eight sessions. A single system design was used to quantitatively determine whether a change had occurred, and to what extent, in the mothers' depressive symptoms and attitude towards mothering at the conclusion of the group intervention. Baseline measures on the Edinburgh Postnatal Depression Scale and the Maternal Attitudes Questionnaire were compared with these scores measured at the conclusion of the intervention. A focus group was held at the conclusion of the intervention to gather qualitative data on the mothers' experience of the group processes and personal outcomes. The results of this study demonstrate that mothers' moods and maternal attitudes improved as a result of this therapeutic group intervention, although they still remained above the diagnostic cut-off threshold for postnatal depression. The intervention was also noted by mothers to be a desirable method of treatment for postnatal depression. Further research is indicated to test whether the positive outcomes hold over a period of time.